2021
DOI: 10.3389/fimmu.2021.689019
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Atlas of Human Deciduas With Unexplained Recurrent Pregnancy Loss

Abstract: Recurrent pregnancy loss (RPL) is a common fertility problem that affects 1%-2% of couples all over the world. Despite exciting discoveries regarding the important roles of the decidual natural killer cell (dNK) and regulatory T cell in pregnancy, the immune heterogeneity in patients with unexplained recurrent pregnancy loss (URPL) remains elusive. Here, we profiled the transcriptomes of 13,953 CD45+ cells from three normal and three URPL deciduas. Based on our data, the cellular composition revealed three maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 73 publications
(100 reference statements)
5
70
0
1
Order By: Relevance
“… Single-cell transcriptomic analysis of decidual CD8+ T cells from publicly available database. (A) UMAP visualization of ∼735 live MS4A7- CD3E+ CD8A+ single cell transcriptomes obtained from the decidua of three healthy first trimester pregnancy samples ( 15 ). Each symbol (circle) represents a cell, and the colors indicate the eight clusters identified by Seurat.…”
Section: Cd8+ T Cell Subsets and Differentiation Trajectories In Deciduamentioning
confidence: 99%
See 3 more Smart Citations
“… Single-cell transcriptomic analysis of decidual CD8+ T cells from publicly available database. (A) UMAP visualization of ∼735 live MS4A7- CD3E+ CD8A+ single cell transcriptomes obtained from the decidua of three healthy first trimester pregnancy samples ( 15 ). Each symbol (circle) represents a cell, and the colors indicate the eight clusters identified by Seurat.…”
Section: Cd8+ T Cell Subsets and Differentiation Trajectories In Deciduamentioning
confidence: 99%
“…This diversification is likely due to the small number of markers that can be simultaneously detected in different biological settings, such as different stages of pregnancy and pathologies, resulting in arbitrary new findings or markers and cytokines, not completely grasping the whole picture. The publicly available single cell RNA sequencing datasets on decidual immune cells include insufficient CD8+ T cells for an in-depth analysis ( 15 ). Therefore, single cell RNA sequencing tailored to CD8+ T cells, e.g.…”
Section: Final Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…The decidua mediates communication between two semiallogenic individuals, the mother and the fetus, which is the epitome of intercellular communication (Iliodromiti et al, 2012;Pavličev et al, 2017). Therefore, the further elucidation of the intercellular communication in the decidua could facilitate our understanding of the fundamental basis of pregnancy and help to reveal pathogenic mechanisms of pregnancy-related disorders (Zhang et al, 2021b;Chen et al, 2021). Intercellular communication network analysis using scRNA-seq of human term placenta has found that the decidua is the center of intercellular signal transduction and has indicated the dominant role of growth factors and immune signals in the intercellular crosstalk (Tsang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%